FBI : Paradox - Book 22 Book 22 - Coulter, Catherine (Waterville, Maine : Thorndike Press, a part of Gale, a Cengage Company, 2018)
Chief Ty Christie of Willicott, Maryland, witnesses a murder at dawn from the deck of her cottage on Lake Massey. When dragging the lake, not only do the divers find the murder victim, they also discover dozens of bones. Even more shocking is the identification of a unique belt buckle found among the bones. Working together with Chief Christie, Savich and Sherlock soon discover a frightening connection between the bones and the escaped psychopath.
"Thorndike Press large print basic"--Title page verso.
Keywords: United States. -- Federal Bureau of Investigation -- Fiction; Sherlock, Lacey (Fictitious character) -- Fiction; Savich, Dillon (Fictitious character) -- Fiction; Escaped prisoners -- Fiction; Serial murder investigation -- Fiction; Suspense fiction; Thrillers (Fiction); Detective and mystery fiction